THE EFFECT OF ROTOR DISC MATERIAL ON TRIBO BEHAVIOR OF AUTOMOTIVE BRAKE PAD MATERIALS - LIEW, K. W.; EL-TAYEB, N. S. M. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
This work aims to investigate the effect of two different counterdisc materials, i.e. gray cast iron (GCI) and ductile gray cast iron (DGCI) on tribo behavior of non-commercial frictional materials (NF1, NF2, NF4, and NF5) and two other chosen commercial brake pads (CMA and CMB) under dry sliding contact conditions. The four non-commercial frictional materials were fabricated with various percentages of phenolic binder resin (15 and 20 vol.%) and reinforced with steel fibers (15 and 20 vol.%) using hot press molding methods. Tribo tests were carried out using a small-scale tribo-tester of pad-on-disc type. Friction coefficient and wear of non-commercial and commercial brake pads were measured against each counterdisc (GCI and DGCI) and compared. Then, the friction and wear characteristic are discussed by comparing the experimental results obtained for each kind of cast iron.